The future of the new artistic innovation in times of social acceleration - Lijster, Thijs 1981-; Bauwens, Lietje 1990- (Valiz, 2018)
In 'The Future of the New' artists, theorists, and professionals working the art field reflect on the role of the arts in a world that is speeding up and changing through joint forces of globalization, digitization, commodification, and financialization. Can artistic innovation still function as a source of critique? How do artists, theorists, and art organizations deal with the changing role of and discourse on innovation? Should we look for alternative ways to innovate, or should we change our discourse and look for other (new!) ways to talk about the new?
Keywords: Kunst; Soziale Funktion; Gesellschaft; Beschleunigung; Aufsatzsammlung